(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The existing personnel training system requires a revision of its content, structure, organization, principles of relationship with educational practice and innovative processes in education. This is directly related to the development of student-oriented educational technologies that ensure the achievement of high quality and guaranteed results of professional training in technical universities. The article discusses the main aspects of the implementation of student-oriented educational technologies in teaching foreign languages.